2013
DOI: 10.1007/s00259-013-2369-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18FDG PET/CT in patients treated with 177Lu-DOTATATE for advanced differentiated neuroendocrine tumours

Abstract: These results suggest that FDG PET evaluation is useful for predicting response to Lu-PRRT in patients with grade 1/2 advanced NETs. Notably, none of PET- patients had progressed at the first follow-up examination after Lu-PRRT. Grade 2 NET and PET+ (arbitrary SUV cutoff >2.5) were frequently associated with more aggressive disease. PET+ patients with grade 2 NET, 32 % of whom did not respond to Lu-PRRT monotherapy, might benefit from more intensive therapy protocols, such as the combination of chemotherapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 27 publications
2
85
1
7
Order By: Relevance
“…However, it has been demonstrated that collection of 18 FGD in neoplastic foci is a negative prognostic factor [90]. The PET/CT scan with 18 FDG, and the assessment of somatostatin receptor expression in a 68 Ga-PET/CT is useful in qualification for radioisotope treatment, particularly in NENs G2 [94].…”
Section: F-fdgmentioning
confidence: 99%
“…However, it has been demonstrated that collection of 18 FGD in neoplastic foci is a negative prognostic factor [90]. The PET/CT scan with 18 FDG, and the assessment of somatostatin receptor expression in a 68 Ga-PET/CT is useful in qualification for radioisotope treatment, particularly in NENs G2 [94].…”
Section: F-fdgmentioning
confidence: 99%
“…The role of 18 F-FDG PET for predicting treatment response was highlighted in a recent study which included G1 or G2 advanced NET, as none of the 18 F-FDG PET-negative patients had progressed at the first follow-up examination after 177 Lu-DOTA-TATE PRRT. In that study population, G2 NET and 18 F-FDG PET positivity were frequently associated with more aggressive disease course [18]. Finally, it seems that avid uptake in 18 F-FDG PET predicts survival.…”
Section: Overview Of Available Molecular Imaging Techniquesmentioning
confidence: 99%
“…Thus, somatostatin receptor imaging (SRI), particularly with 68 Ga-SMS-R-PET, alters management in >50 % and successfully predicts response to cold or radiolabeled analogues [10,11]. Although conventional 18 fludeoxyglucose (FDG) PET is not a primary diagnostic tool in NETs, standardized uptake value (SUV) assessment can provide predictive information in terms of progression-free survival and response to peptide receptor radiotherapy (PRRT) [12,13].…”
Section: Strength Of Each Techniquementioning
confidence: 99%
“…In parallel, its correlation with the tumor Ki67 index, the transcript proliferome or other indices of proliferation have not been adequately delineated. For example, 18 FDG is positive in a substantial percentage of slow-proliferating low grade (G1) tumors, confounding the generally accepted notion that it is only useful in the identification of rapidly proliferating and poorly differentiated tumors [13].…”
mentioning
confidence: 99%